2015
DOI: 10.3109/19401736.2015.1079904
|View full text |Cite
|
Sign up to set email alerts
|

The expression characteristics of mt-ND2 gene in chicken

Abstract: Subunit 2 of NADH dehydrogenase (ND2) is encoded by the mt-ND2 gene and plays a critical role in controlling the production of the mitochondrial reactive oxygen species. Our study focused on exploring the mt-ND2 tissue expression patterns and the effects of energy restriction and dietary fat (linseed oil, corn oil, sesame oil or lard) level (2.5% and 5%) on its expression in chicken. The results showed that mt-ND2 gene was expressed in the 15 tissues of hybrid chickens with the highest level in heart and lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…This suggests that higher expression of muscle avPGC-1A is an indicator of slower growth. ND2 is another gene that controls the production of the mitochondrial ROS and is negatively affected by high dietary fat content and bird aging ( Zhang et al., 2016 ). The results from this study demonstrated that the level of muscle ND2 mRNA expression was higher in the LCP- than the SCP-fed birds.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that higher expression of muscle avPGC-1A is an indicator of slower growth. ND2 is another gene that controls the production of the mitochondrial ROS and is negatively affected by high dietary fat content and bird aging ( Zhang et al., 2016 ). The results from this study demonstrated that the level of muscle ND2 mRNA expression was higher in the LCP- than the SCP-fed birds.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial complex V consists of 19 genes in human. The function of genes involved in complex I and V has been reported, such as mt-ND2 [ 19 ], ATP5E [ 20 ], and ATP5G3 [ 21 , 22 ]. Subunit 2 of NADH dehydrogenase (ND2) is one of genes comprising of mitochondrial complex I [ 23 ], which plays a critical role in controlling the production of the mitochondrial reactive oxygen species in chicken [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subunit 2 of NADH dehydrogenase (ND2) is one of genes comprising of mitochondrial complex I [ 23 ], which plays a critical role in controlling the production of the mitochondrial reactive oxygen species in chicken [ 24 ]. Mt-ND2 gene was extensively expressed in tissues, and the expression was affected by dietary fat types and chicken age [ 19 ]. The altered expression of mt-ND2 is critical to multiple disease in human [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jha et al [24]discovered 338 DEGs in the RNA-seq dataset of lung epithelial cells infected with SARS-CoV-2, including 92 increased and 246 decreased genes across the datasets. In this study, top abundant DEGs such as genes encoding for ribosomal protein (RPL4), controlling the production of the mitochondrial reactive oxygen species (MT-ND2) [25], modulating cell proliferation and differentiation (SCD5) [26], mitochondrial deficiencies, and associated disorders (MT-CYB) [27], epithelial marker ezrin (EZR) associated with cell surface structure adhesion, migration, and organization of the SARS-CoV-2 [28] were found to be co-expressed in the nasopharyngeal epithelial cells of COVID-19 patients and recovered humans (Fig. 2C).…”
Section: Discussionmentioning
confidence: 99%